Japanese culture and the morals / Tomonari Tsuchiya - Tomonari, Tsuchiya (Faculty of Music, 2017)
Relies of instrumental techniques and timbre along with poetic songs and plays. Each instruments has fixed tuning. Limited numbers of tunings.melodies are mainly modal and homophonic.